2022
DOI: 10.3389/fceng.2022.1059160
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of multiphase reactions under microwave irradiation: A mini-review

Abstract: Microwave (MW) heating is rapid, selective, and volumetric, and it is a compelling non-conventional heating approach for driving chemical reactions. The effect of MW irradiation on the kinetics of thermal/catalytic reactions is still under debate. A group of researchers reported that the effect of MW heating on reaction kinetics is highlighted through the non-thermal effects of MWs on kinetic parameters and reaction mechanisms in addition to the thermal effect. However, another group attributed the observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Some studies reported that kinetic parameters change under MW heating due to the nonthermal effect of MW heating in addition to the thermal effect . However, results presented in Figure show that nonuniformity in heat dissipation inside the reactor can result in the underestimation/overestimation of temperature.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Some studies reported that kinetic parameters change under MW heating due to the nonthermal effect of MW heating in addition to the thermal effect . However, results presented in Figure show that nonuniformity in heat dissipation inside the reactor can result in the underestimation/overestimation of temperature.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, the presence of elements/compounds with different dielectric properties in the solid phase and applying hybrid heating, i.e., employing an MW absorber, such as SiC or activated carbon, for heating materials that have poor interactions with MWs, can result in microscale hotspots. They can, accordingly, affect apparent kinetic parameters …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations